We Can Believe the Error Theory - Lillehammer, Hallvard (Ethical theory and moral practice, 2015)
Bart Streumer argues that it is not possible for us to believe the error theory, where by error theory he means the claim that our normative beliefs are committed to the existence of normative properties even though such properties do not exist. In this paper, we argue that it is indeed possible to believe the error theory. First, we suggest a critical improvement to Streumers argument. As it stands, one crucial premise of that argumentthat we cannot have a belief while believing that there is no reason to have itis implausibly strong. We argue that for his purposes, Streumers argument only requires a weaker premise, namely that we cannot rationally have a belief while believing that there is no reason to have it. Secondly, we go on to refute the improved argument. Even in its weaker form, Streumers argument is either invalid or the crucial premise should be rejected.